HADITH AND PROPHET MUHAMMAD AUTHORITY: Understanding of Jonathan A.C. Brown - Nafisah, Lailiyatun (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2022)
Hadith is frequently the subject of research by Muslim academics and Westerners. Both Muslim academics and orientalists have debated the legitimacy of the hadith for a long time. Jonathan AC Brown is a western Muslim scholar who contributes to rationally explaining the study of hadith so that it is easily accepted by beginners; his work demonstrates his commitment to the study of Islamic studies. This study follows a library research approach in which Jonathan Brown's book